2016
DOI: 10.1039/c5cp04960a
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition behaviors of the supported DPPC bilayer investigated by sum frequency generation (SFG) vibrational spectroscopy and atomic force microscopy (AFM)

Abstract: The phase transition behaviors of a supported bilayer of dipalmitoylphosphatidylcholine (DPPC) have been systematically evaluated by in situ sum frequency generation (SFG) vibrational spectroscopy and atomic force microscopy (AFM). By using an asymmetric bilayer composed of per-deuterated and per-protonated monolayers, i.e., DPPC-d75/ DPPC and symmetric bilayer of DPPC/DPPC, we were able to probe the molecular structural changes during the phase transition process of the lipid bilayer by SFG spectroscopy. It w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 56 publications
(141 reference statements)
4
59
0
Order By: Relevance
“…33,3746 To investigate the influence of defects on flip-flop, we performed random-walk (Monte Carlo) simulations of lateral lipid diffusion in the presence of 100 nm-diameter holes, a typical size observed in AFM images. 46 Figure 4a shows a schematic illustration of such a defect (not to scale) in a supported bilayer. We assumed that translocation effectively occurs by unhindered lateral diffusion of a lipid through the pore formed by the lipid headgroups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…33,3746 To investigate the influence of defects on flip-flop, we performed random-walk (Monte Carlo) simulations of lateral lipid diffusion in the presence of 100 nm-diameter holes, a typical size observed in AFM images. 46 Figure 4a shows a schematic illustration of such a defect (not to scale) in a supported bilayer. We assumed that translocation effectively occurs by unhindered lateral diffusion of a lipid through the pore formed by the lipid headgroups.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, AFM images of SSB generally show numerous patches of bare substrates appearing as holes with submicron dimensions (tens to hundreds of nanometers in diameter); these are especially ubiquitous in gel-phase bilayers. 33,3746 Moreover, for typical values of bilayer surface coverage, the average distance between holes is on the order of microns or less. 46 Although these defects are often too small to be seen with conventional fluorescence microscopy, they can be detected with other fluorescence techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phase transitions in single SLBs have been addressed mainly by means of AFM (atomic force microscopy) [11][12][13][14], SFG-VS (sum-frequency generation vibrational spectroscopy) [14], MD (molecular dynamics) simulations [15], and calorimetry [16]. The main common result is a substantial broadening of the gel-to-fluid phase transition (PT) with respect to that observed in freestanding bilayers in solution.…”
mentioning
confidence: 99%
“…The main common result is a substantial broadening of the gel-to-fluid phase transition (PT) with respect to that observed in freestanding bilayers in solution. In some cases, AFM and calorimetry measurements have shown a decoupling between the PT behavior of the portion of the SLB facing the solid substrate (proximal leaflet) and the one closer to the water subphase (distal leaflet) [13,14,16]. In particular, Xie and co-workers [11] reported that the gel-to-fluid PT in a single DMPC (1,2-dimyristoyl-sn-glycero-3-phosphocholine) SLB is characterized by the formation and subsequent growth of fluid domains as the temperature is increased; coexistence between gel and fluid phases was observed in the central part of the PT, until the growing domains entirely replaced the starting phase.…”
mentioning
confidence: 99%